Spray Drying of Rhodomyrtus tomentosa (Ait.) Hassk. Flavonoids Extract: Optimization and Physicochemical, Morphological, and Antioxidant Properties. (4th December 2014) - Wu, Pingping; Deng, Qian; Ma, Guangzhi; Li, Nianghui; Yin, Yanyan; Zhu, Baojun; Chen, Meiling; Huang, Ruqiang
Abstract : The optimal condition of spray drying purified flavonoids extract from R. tomentosa berries was studied by response surface methodology. The optimized condition for microencapsulation was of maltodextrin to gum Arabic ratio 1 : 1.3, total solid content 27.4%, glycerol monostearate content 0.25%, and core to coating material ratio 3 : 7, resulting in EE 91.75%. Prepared at the optimized condition, the flavonoids extract microcapsules (FEMs) were irregularly spherical particles with low moisture content (3.27%), high solubility (92.35%), and high bulk density (0.346 g/cm 3 ). DPPH radical scavenging activity of FEMs was not decreased after spray drying (P > 0.05 ) and higher than those in citric acid and rutin at the same concentration. Moreover, FEMs effectively retarded the oxidation of fresh lard during the 10-day storage period compared with vitamin C, nonencapsulated flavonoids extract, and rutin. Therefore, FEMs produced at the optimized condition could be used as powder ingredients with antioxidant capacities.